Przekłady literatury polskiej w Słowenii w 2015 roku - Muszyńska Vizintin, Anna (Przekłady Literatur Słowiańskich, 2016)
Polish literature in Slovenian translation in 2015 In 2015, fifteen Polish books were translated into Slovenian, which is almost twice as much when compared to 2014. Prose has been dominant; Polish poetry was represented by two poets of different generations: Tadeusz Różewicz, whose two collections (Profesorjev nožek and Siva Zona) were translated by the experienced translator Jana Unug. Furthermore, Justyna Bargielska, a young Polish poetess, whose poetry selection entitled Serija manjših ran was prepared by Staša Pavlović. Interestingly, in 2015 Slovenes translated six books for children and young readers (Onichimowska, Maleszka, Żółtowska -Yvette) and two books on religious topics (Ewa Czaczkowska’s Sestra Faustina and John Paul II’s personal notes from 1962 to 2003). The varied selections, translators’ offerings and the growing number of Slovenian translations of Polish literature (which were mostly published by very prestigious companies such as Beletrina, Družina, Modrijan and Cankarjeva Založba) demonstrate that Slovenian readers are interested in Polish culture and interested in reading Polish books. Key words: translations in 2015, translation choices, intercultural dialogue.